Math, asked by bhavyarajrathore08, 3 months ago

plz give answer with full solution...
Right answer with correct solution will be mark as Brainliest...​​

Attachments:

Answers

Answered by mathdude500
20

Appropriate Question :-

\rm :\longmapsto\:If \:  \: x =  \dfrac{5 -  \sqrt{21}}{2}, \: prove \: that

\red{\rm \:\bigg( {x}^{3}   + \dfrac{1}{ {x}^{3} } \bigg)  - 5\bigg( {x}^{2}   + \dfrac{1}{ {x}^{2} } \bigg) + \bigg( x + \dfrac{1}{x} \bigg) = 0}

\large\underline{\sf{Solution-}}

Given that

\rm :\longmapsto\:x =  \dfrac{5 -  \sqrt{21}}{2}

So, Let consider,

\rm :\longmapsto\:\dfrac{1}{x}

\rm \:  =  \:  \: \dfrac{2}{5 -  \sqrt{21} }

On rationalizing the denominator, we get

\rm \:  =  \:  \: \dfrac{2}{5 -  \sqrt{21} }  \times \dfrac{5 +  \sqrt{21} }{5 +  \sqrt{21} }

\rm \:  =  \:  \: \dfrac{2(5 +  \sqrt{21} )}{ {5}^{2} -  {( \sqrt{21}) }^{2}  }

\rm \:  =  \:  \: \dfrac{2(5 +  \sqrt{21} )}{ 25 - 21}

\rm \:  =  \:  \: \dfrac{2(5  + \sqrt{21} )}{4}

\rm \:  =  \:  \: \dfrac{5  + \sqrt{21} }{2}

Hence,

\rm :\longmapsto\:x + \dfrac{1}{x}

\rm \:  =  \:  \: \dfrac{5 -  \sqrt{21} }{2}  + \dfrac{5 +  \sqrt{21} }{2}

\rm \:  =  \:  \: \dfrac{5 -  \sqrt{21}  + 5 +  \sqrt{21} }{2}

\rm \:  =  \:  \: \dfrac{10}{2}

\rm \:  =  \:  \: 5

Hence,

\red{\rm :\longmapsto\:x + \dfrac{1}{x}  = 5}

Now,

\rm :\longmapsto\: {x}^{2} + \dfrac{1}{ {x}^{2} }

\rm \:  =  \:  \:  {\bigg(x + \dfrac{1}{x} \bigg) }^{2}  - 2

\rm \:  =  \:  \:  {5}^{2}  - 2

\rm \:  =  \:  \:  25  - 2

\rm \:  =  \:  \:  23

Now, Consider

\rm :\longmapsto\: {x}^{3} + \dfrac{1}{ {x}^{3} }

\rm \:  =  \:  \:  {\bigg(x + \dfrac{1}{x} \bigg) }^{3}  - 3\bigg(x - \dfrac{1}{x} \bigg)

\rm \:  =  \:  \:  {(5)}^{3} - 3 \times 5

\rm \:  =  \:  \: 125 - 15

\rm \:  =  \:  \: 110

Now, Consider

\red{\rm :\longmapsto\:\bigg( {x}^{3}   + \dfrac{1}{ {x}^{3} } \bigg)  - 5\bigg( {x}^{2}   + \dfrac{1}{ {x}^{2} } \bigg) + \bigg( x + \dfrac{1}{x} \bigg)}

\rm \:  =  \:  \: 110 - 5(23) + 5

\rm \:  =  \:  \: 110 - 115 + 5

\rm \:  =  \:  \: 0

Hence, proved

Identities Used :-

\rm :\longmapsto\: {x}^{3} + \dfrac{1}{ {x}^{3} } =  \:  \:  {\bigg(x + \dfrac{1}{x} \bigg) }^{3}  - 3\bigg(x - \dfrac{1}{x} \bigg)

\rm :\longmapsto\: {x}^{2} + \dfrac{1}{ {x}^{2} } =  \:  \:  {\bigg(x + \dfrac{1}{x} \bigg) }^{2}  - 2

\red{\rm :\longmapsto\:(x + y)(x - y) =  {x}^{2} -  {y}^{2}}

Similar questions